Transcriptome-wide Dynamics of m6A mRNA Methylation During Porcine Spermatogenesis - Zidong Liu; Xiaoxu Chen; Pengfei Zhang; Fuyuan Li; Lingkai Zhang; Xueliang Li; Tao Huang; Yi Zheng; Taiyong Yu; Tao Zhang; Wenxian Zeng; Hongzhao Lu; et al. (Genomics, Proteomics & Bioinformatics, 2023)
Spermatogenesis is a continual process that occurs in the testes, in which diploid spermatogonial stem cells (SSCs) differentiate and generate haploid spermatozoa. This highly efficient and intricate process is orchestrated at multiple levels. N6-methyladenosine (m6A), an epigenetic modification prevalent in mRNAs, is implicated in the transcriptional regulation during spermatogenesis. However, the dynamics of m6A modification in non-rodent mammalian species remains unclear. Here, we systematically investigated the profile and role of m6A during spermatogenesis in pigs. By analyzing the transcriptomic distribution of m6A in spermatogonia, spermatocytes, and round spermatids, we identified a globally conserved m6A pattern between porcine and murine genes with spermatogenic function. We found that m6A was enriched in a group of genes that specifically encode the metabolic enzymes and regulators. In addition, transcriptomes in porcine male germ cells could be subjected to the m6A modification. Our data show that m6A plays the regulatory roles during spermatogenesis in pigs, which is similar to that in mice. Illustrations of this point are three genes (SETDB1, FOXO1, and FOXO3) that are crucial to the determination of the fate of SSCs. To the best of our knowledge, this study for the first time uncovers the expression profile and role of m6A during spermatogenesis in large animals and provides insights into the intricate transcriptional regulation underlying the lifelong male fertility in non-rodent mammalian species.